Endoscopic Adenoidectomy with Microdebrider Versus Conventional Adenoidectomy - Das, Sanjoy; Dutta, Pranay Kumar; Sen, Tuli (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Adenoidectomy is one of the most common surgical procedures performed in children in Bangladesh. Though conventional curettage is highly popular as it has the advantage of being cost effective and continues to be a commonly used method especially in developing countries but Microdebrider has opened the new horizon in this arena. To compare conventional curettage adenoidectomy and endoscopic-assisted powered adenoidectomy using a microdebrider. Materials and methods: This is randomized single blinded comparative study, which was performed in the Medical Center Hospital, Chattogram from August 2019 to July 2020. A total of 60 patients were randomly divided into two groups. Group I underwent conventional curettage adenoidectomy while Group II underwent endoscopic- assisted powered adenoidectomy. Duration of surgery, amount of intra-operative bleeding, adequateness of removal and damage to the adjacent structures were assessed and compared between two groups. All patients were followed for 12 months. Statistical analysis was done using statistical software package SPSS v 22.0. Data were represented as mean ± SD. Continuous variables were compared using the were using the t test while nonparametric data were compared using Mann-Whitney U test. The c2 test was used to compare the nominal data. A p value <0.05 was considered statistically significant. Ethical directives from the Managing Body of Medical Centre Hospital, Chattogram for this study was obtained. Results: in our study, we observed approximately almost three times more mean blood loss and total operating time in the endoscopic-assisted powered procedure compared to the conventional technique (149 and 56 ml, respectively, 63 and 27 min, respectively). Nine (30%) cases in group I had more than 50% residual adenoid tissue while 20 – 50% of residual adenoid tissue was documented among 7 patients (23%). Postoperative pain was found to be significantly higher in group I compared to group II. In both groups, recovery time ranged from 24-48 hour with a mean of 33.6 hour in group I and 36 hour for group II. 23 patients (77%) in group I presented with residual disease in the 3 months follow up period, where number of patients with the exact instance in group II was 0. Conclusion: Endoscopic assisted adenoidectomy may appear more handy over conventional curettage. But precise peri-operative care and awareness are required to attain the successful outcomes. JCMCTA 2022 ; 33 (1) : 88-92